On the Definition of Terms in a Requirements Expression. Issue 1 (28th October 2015) - Ryan, Michael J.; Wheatcraft, Louis S.; Dick, Jeremy; Zinni, Richard
Abstract: The purpose of a requirement expression is to communicate clearly the needs of various entities into a formal language such that the intent is clearly understood by all involved: those whose job it is to implement the requirement, those responsible for proving the built system meets the requirement, and those responsible for proving the resulting system meets the needs of the relevant entity. Although many sources provide definitions of the terms associated with a requirement expression, there are only occasional agreements on common definitions, and the defined terms are too narrowly focused to be useful across the full requirements engineering domain. This paper proposes a cohesive set of definitions of the terms associated with a requirement expression. First, a framework for the transformation of needs into requirements is briefly discussed and existing definitions are presented from major relevant sources. These definitions are then analyzed and a cohesive set of definitions is offered for the key terms associated with a requirements expression: entity; need; requirement statement; and the requirement attributes that, along with the requirement statement itself, comprise the requirement expressions in a requirement set.